STUDI FENOMENOLOGI PENGEMUDI OJEK ONLINE PEREMPUAN DI KOTA BANDUNG DALAM KAJIAN FEMINISME - Irma Verasatiwi; Roro Retno Wulan (Jurnal Ilmu Komunikasi Acta Diurna, 2018)
In today's era of modernization, women prefer to work rather than just housewives, although the workthey choose is not suitable for women. Stereotypes in societies that still assume that women areunsuited for work are increasingly faded by women themselves. They demonstrate the existence andquality of self in order to be accepted in society and to get the recognition that they are worth equallyby men. The development of the world of technology that increasingly facilitate the community indoing all activities to make other aspects of progress as well, including ease in the world oftransportation. Currently, people easily order transportation such as taxis and motorcycles only byusing the application. It is also what motivates women to show the existence and quality of self in theenvironment by doing a profession commonly done by men, which is an online motorcycle taxi driver.Although initially it is considered taboo, but the online motorcycle taxi drivers increasingly prove thatit is not feasible to be a parameter in assessing women.